Review: Split Beam Echo Sounder in Acoustic Systems for Determine Abundance of Fish in Marine Fisheries - Lubis, Muhammad Zainuddin; Surya, Ganda; Timbang, Dirgan; Rizki, Fajar; Ardian, Sandi; Hanafi, Aditya; Ariwinata Saragih, Diaz; Pradipta Ramdhani, Bayu; Novanto, Perdi; Ependi, Fikriansyah; Nofranda, M Andrew; Apriliani, Dhilla; Lestari Situmorang, Arini Dewi (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2017)
In the ocean, acoustic waves are transmitted into the subsurface ocean will experience scattering (scattering) caused by marine organisms, material distributed, the structure is not homogeneous in seawater, as well as reflections from the surface and the seabed. Estimation of fish stocks in the waters wide as in Indonesia have a lot of them are using the acoustic method. The acoustic method has high speed in predicting the size of fish stocks so as to allow acquiring data in real time, accurate and high speed so as to contribute fairly high for the provision of data and information of fishery resources. Split beam echo sounder comprises two aspects, and a transducer. The first aspect is the high-resolution color display for displaying echogram at some observations and also serves as a controller in the operation of the echo sounder. The second aspect is transceiver consisting of transmitter and receiver. The echosounder divided beam first inserted into the ES 3800 by SIMRAD beginning of the 1980s and in 1985 was introduced to fishermen in Japan as a tool for catching up. Split beam transducer is divided into four quadrants. Factors that contribute affect the value of Target Strength (TS) fish Strength target can generally be influenced by three factors: a target factor itself, environmental factors, and factors acoustic instrument.